Oral colon-targeted responsive chitosan/pectin-based nanoparticles propels the application of tofacitinib in colitis therapy - Chunfei Wu; Chuanlin Bi; Geun-soo Kim; Zizhen Yang; Shuao Li; Tong Dai; Xiaoyu Wu; Jiaojiao Tan; Ningning He; Shangyong Li (Scientific Reports)
Abstract Tofacitinib (Tof), a commercially available pan-Janus kinases inhibitor, is approved for the treatment of moderate to severe ulcerative colitis. However, its clinical application is limited due to dose-dependent systemic side effects. The present study aims to develop an efficient oral colon-targeted drug delivery systems using prebiotic pectin (Pcn) and chitosan (Csn) polysaccharides as a shell, with Tof loaded into a Bovine Serum Albumin (BSA) core, and improving it with chondroitin sulfate (Chs), thus constructing Tof@BSA-Chs-CP nanoparticles (NPs). Our results suggest that the pH-sensitive characteristics of the Pcn/Csn shell contribute to its capacity for attenuating absorption and systemic diffusion in the gastrointestinal tract, and exhibiting targeted localization at inflamed colonic sites in mice. Additionally, the gut microbiota-secreted polysaccharide-degrading enzyme acts as the triggering agent for Pcn/Csn shell degradation. In mice colitis models, we demonstrated that oral administration of Tof@BSA-Chs-CP NPs effectively ameliorated colitis and expedited its resolution by modulating the expression of pro-inflammatory cytokines and immune regulatory factors. Collectively, our synthetic NPs demonstrate the promising potential of Tof for the therapy of UC.